Anti-Drug Policies in Different Countries and Georgia: Current Situtation and Challenges - Shota Tkeshelashvili (European Scientific Journal, ESJ, 2022)
Problems with illegal drug circulation have even become a destabilizing factor for many countries. Therefore, the topic under consideration is undoubtedly problematic. The present article according to qualitative research method focuses on the current situation, challenges and ways of solving problems regarding the drug policy in Georgia and some foreign countries. The research has shown that the problems connected to the drugs (use, sale, transportation and etc) are common to many countries and according to the existing reality, it will probably be a topic issue for a long time not only for Georgia, but also in many countries around the world. Determination of effective drug policy in Georgia is one of the most pressing problems and tasks, but resolving of issue of adequate and proper responsibility for drug use is the most urgent matter.